2016
DOI: 10.1186/s12884-016-0933-9
|View full text |Cite
|
Sign up to set email alerts
|

Identification of fetal cardiac anatomy and hemodynamics: a novel enhanced screening protocol

Abstract: BackgroundPrenatal cardiac screening is of great importance as it contributes to appropriate neonatal management and helps parents to make a decision regarding their pregnancy. The aim of our study was to evaluate the efficiency of a newly proposed screening protocol in the detection of fetal congenital heart disease (CHD).MethodsThis was a prospective study. A total of 52 cases of confirmed CHD fetuses and 248 cases of randomly selected normal fetuses were included in the study. Two sonographers with similar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Therefore, fetal echocardiography guidelines in Japan suggest that another fetal heart screening be performed at approximately 30 GW. A recent paper has revealed that the use of color Doppler may lead to improved detection rates for valvular abnormalities, and color Doppler may therefore be useful in fetal cardiac screening.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, fetal echocardiography guidelines in Japan suggest that another fetal heart screening be performed at approximately 30 GW. A recent paper has revealed that the use of color Doppler may lead to improved detection rates for valvular abnormalities, and color Doppler may therefore be useful in fetal cardiac screening.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of a color Doppler evaluation of the fetal heart during routine second-trimester sonography in low-risk patients had been reported to improve the detection rates for valvular abnormalities including PS. 32 33 Our findings can be used to improve prenatal detection of isolated VSD and PS in a low-risk population. In women with low PAPP-A, high AFP, or high inhibin-A, even if major heart abnormalities are not found on detailed sonography in the second trimester, efforts might be continued to find CHDs including isolated VSD or PS using an additional ultrasonogram with or without color Doppler.…”
Section: Discussionmentioning
confidence: 88%
“…The Routine Antenatal Diagnostic Imaging with Ultrasound (RADIUS) experiment found that the diagnostic accuracy of anatomical abnormalities in the non teaching environment is lower (9). The demonstration of the left and right ventricular outflow pathways takes more time and demands even greater expertise.…”
Section: Discussionmentioning
confidence: 99%